Geohazard features of the north-western Sicily and Pantelleria - Attilio Sulli; Marilena Calarco; Mauro Agate; Ludovico Albano; Alessandro Bosman; Giuseppe Di Grigoli; Francesco Gargano; Valeria Lo Presti; Eleonora Martorelli; Valentina Pennino; Andrea Sposato; Elisabetta Zizzo; et al. (Journal of Maps)
We present maps of geohazard features identified across north-western Sicily and Pantelleria in the framework of the Magic project (MArine Geohazard along Italian Coasts), which involved Italian marine geological researchers in 2007-2013. These seafloor features were recognized using high-resolution bathymetry data and rely on the morphological expression of the seafloor and shallow sub-surface processes. The north-western Sicily is a complex continental margin, affected by morphodynamic, depositional, and tectonic processes. The Egadi offshore is controlled by fault escarpments and alternating retreating and progradational processes. Ustica and Pantelleria submerged edifices show the effect of volcanic activity. The Ustica seafloor is interested in volcanic, tectonic, and gravitational instability processes, while the Pantelleria offshore underwent erosive-depositional processes and the effect of bottom currents. Two levels of interpretation are represented: the physiographic domain at a scale of 1:250.000 and the morphological units and morpho-bathymetric elements at a 1:100.000 scale.